Profil Kecerdasan Majemuk dan Karakteristik Mahasiswa Fakultas Ilmu Pendidikan Universitas Negeri Medan: Studi Deskriptif Kuantitatif - Khairani, Fitri; Harahap, Siti Arafah; Fadilla, Siti; Apriliana, Mitha; Desianti, Nur Salsabilla (Veritas: Jurnal Penalaran dan Riset Mahasiswa Pendidikan, 2026)
This study aims to describe the profile of multiple intelligences and the characteristics of students at the Faculty of Education, Universitas Negeri Medan. A quantitative descriptive method was employed involving 25 students from four study programs: Elementary School Teacher Education, Early Childhood Teacher Education, Guidance and Counseling, and Community Education. The sample was selected using purposive sampling to ensure representation from each program. Data were collected using the Multiple Intelligences Score questionnaire based on Howard Gardner’s theory and a character assessment instrument. Data collection was conducted both online and offline, and the data were analyzed using descriptive statistics with the assistance of Jamovi software. The results indicate that the majority of respondents were female students aged 18–21 years with relatively homogeneous demographic and academic characteristics. The average cumulative grade point average was 3.60, indicating good academic achievement. Students spent an average of 3.60 hours per day using social media, which may contribute to the development of interpersonal and visual intelligences when managed appropriately. Most students lived in boarding houses located near the campus, supporting independence and social adaptability. The findings suggest that students possess diverse forms of intelligence that extend beyond academic achievement, supporting the concept of multiple intelligences. Therefore, it is recommended that learning processes in higher education be designed to accommodate and develop various types of student intelligences optimally.